1991
DOI: 10.1007/bf01690773
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of the biox 3700 pulse oximeter in patients receiving vasoactive therapy

Abstract: The accuracy of pulse oximetry for the prediction of oxygen saturation of arterial blood in patients with shock has been hardly studied. This study was undertaken to determine if O2 arterial saturation estimated by the Biox 3700 pulse oximeter (SpO2) with an ear probe could reliably substitute for the measurements of O2 saturation (HbO2) with an IL-282 Co-Oximeter in samples of arterial blood obtained from 24 caucasian patients. All patients were mechanically ventilated and needed vasoactive drugs (dopamine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Different studies show a wide range (Ϫ0.02 to 3.39) of bias between the oxygen saturation assessed by pulse oximetry and arterial blood gas analysis (Table 4). [2][3][4][13][14][15][16] This may in part be due to the different clinical situations in which the studies were performed and the fact that the pulse oximeter interprets the ratio of oxyhemoglobin to total hemoglobin in the pulsatile arterial vessels. 17 Therefore, factors altering the detection of pulsatility of the arteries limit the accuracy of the S pO 2 values.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…Different studies show a wide range (Ϫ0.02 to 3.39) of bias between the oxygen saturation assessed by pulse oximetry and arterial blood gas analysis (Table 4). [2][3][4][13][14][15][16] This may in part be due to the different clinical situations in which the studies were performed and the fact that the pulse oximeter interprets the ratio of oxyhemoglobin to total hemoglobin in the pulsatile arterial vessels. 17 Therefore, factors altering the detection of pulsatility of the arteries limit the accuracy of the S pO 2 values.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…Both the degree of inaccuracy, or bias, and its direction has been inconsistent [1-3,5,7-9]. In addition, while certain studies of critically ill patients have demonstrated that hypoxemia [1], anemia [10], requirement for vasoactive drugs [7], and acidosis [8] influence the accuracy of pulse oximetry, others have not [2,6]. Data on the effects of other physiologic derangements, such as hyperlactatemia and bacteremia, are absent.…”
Section: Introductionmentioning
confidence: 99%
“…This has also been demonstrated in animal models of severe sepsis [14,15]. The two existing studies examining the performance of pulse oximetry in humans with septic shock [7,9] were small, consisting of a combined 17 patients, and were undertaken in the intensive care unit (ICU), later in the course of disease. As the pathophysiology of sepsis evolves over time, with its distinct temporal changes to hemodynamic [16] and inflammatory [17] variables, there is an important paucity of data regarding pulse oximeter accuracy early in the course of severe sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of pulse oximetry during hypoxemia has been studied during breathing of hypoxic gas mixtures by healthy volunteers and in children with cyanotic congenital heart disease [3,4]. The effect of low perfusion on pulse oximetry has been studied using vasoconstrictive therapy, during hemorrhagic hypotension and in sepsis-associated hypoperfusion [5,6,7]. …”
Section: Introductionmentioning
confidence: 99%